Anti-microbial activity of aqueous exyracts from selected Philippine soft coral species - Aguilar, Remotito A.
Five species of soft corals were collected from Taklong Islands Guimaras and then extracted with water. The aqueous extract was assayed for anti-microbial activity. Potent extracts were tested for its minimal inhibitory concentration against the most sensitive microorganisms. The equivalent potency was also determined using PEN VK as the standard antibiotic. Lobophyton was found to inhibit S. aureus at 50% concentration of the aqueous extract (ATCC 25923) while Sinularia sp. was found to inhibit the growth of both S. aureus (ATC 25923) and B. subtilis (NSRI -1). Aqueous extract of Lobophyton sp., has an equipotency of 6.64 units/ml of PEN VK against S. aureus whereas aqueous extract of Sinularia sp. has a potency of 104 units/ml of PEN VK against B. subtilis.